Politiche del lavoro e azioni regionali: modelli di capitalismo tra eredità storica e capacità di innovazione - Lucciarini, Silvia (Cambio. Rivista sulle Trasformazioni Sociali, 2017)
The paper shows the Institutional complementarities between active and passive labour market policies and welfare regime in a regional perspective. The aim is to explore the different outcomes in terms of growth and cohesion in the Italian regions, using a quali-quantitative analisys. A multilevel approach is developed, looking how the national regulation frame affects the local one, and how specific territorial outcomes depend on institutional and integration policy issues. It’s underpinned how the cognitive embeddedness determines patterns in local actor’s measures and frames.